The effect of aerobic exercise and herbal capsule (hydro-alcoholic extract of Valeriana jatamansi Jones ex Roxb. and Melissa officinalis L.) on changes in serotonin levels and headache indices in women with chronic tension-type headache - Zohreh Eskandari; Ghazale Mohammadi (Institue of Medicinal Plants, ACECR, 2023)
Background: Tension headache is the most common type of headache. Objective: The purpose of this study was to investigate the effect of aerobic exercise and herbal capsules on serotonin levels and headache indices in women suffering from chronic tension-type headache (CTTH). Methods: In this practical study, 18 adult female patients with CTTH were randomly divided into two equal groups: exercise and herbal capsule. Aerobic training was performed three sessions a week, each session lasting 75 minutes for eight week. The herbal capsule contained the hydro-alcoholic extract of Valeriana jatamansi and Melissa officinalis. Each capsule contained 280 mg of these two herbs, which the patients consumed three times a day. Serotonin levels, headache indices (intensity, duration, and frequency of headache), anxiety, depression, use of synthetic drugs, and aerobic capacity were evaluated at baseline and at the end of the study. Results: According to the results within the group, in both groups there was a significant increase in serotonin, aerobic capacity (only in the exercise group) and a significant decrease in anxiety, depression, headache intensity, headache frequency, headache duration (only in the exercise group) and the use of synthetic drugs. In the comparison between groups, a significant difference was observed in the intensity and frequency of headache, use of synthetic drugs, aerobic capacity and anxiety. Conclusion: Aerobic exercise and hydro-alcoholic extract of Valeriana jatamansi and Melissa officinalis plants can be a suitable treatment supplement for women suffering from CTTH but the effect of two plants was better in improving headache.